1980
DOI: 10.1093/ajcn/33.4.887
|View full text |Cite
|
Sign up to set email alerts
|

History of nightblindness: a simple tool for xerophthalmia screening

Abstract: Among 5925 preschool-age children examined in a house to house rural field study, X1B (Bitot's spot with xerosis) and/or an history of nightblindness (XN) was presented in 325. Mean serum vitamin A levels among those with isolated XN (13.9 microgram/dl), isolated X1B (13.4 micrograms/dl), and coexistent XN/X1B (12.1 microgram/dl) were similar, and significantly below that of normal age/sex/neighborhood matched controls (17.6, 17.1, and 18.3 microgram/dl, respectively). The mean serum vitamin A level of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
5

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 0 publications
2
35
1
5
Order By: Relevance
“…The literal translation of kwak moin in Cambodian is 'chicken blindness.' A history of nightblindness has been shown to be a reliable indicator of vitamin A deficiency in surveys (Sommer et al, 1980). Other questions included a history of diarrhea in the last 2 weeks, consumption of eggs, dark-green leafy vegetables, carrots, ripe papaya, ripe mango, pumpkin, sweet potato, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The literal translation of kwak moin in Cambodian is 'chicken blindness.' A history of nightblindness has been shown to be a reliable indicator of vitamin A deficiency in surveys (Sommer et al, 1980). Other questions included a history of diarrhea in the last 2 weeks, consumption of eggs, dark-green leafy vegetables, carrots, ripe papaya, ripe mango, pumpkin, sweet potato, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Sommer et al (1981) found that, in Indonesia, between two and five pre-school children per 1000 had nutritional corneal lesions, and fifty-five per 1000 had conjunctival xerosis (XIA) plus Bitot's spot (XIB) with a history of night blindness (XN; Sommer et al 1978). It has been reported by the Institute of Nutrition and Food Science, University of Dhaka (1977), that in 90% of families in Bangladesh the intake of vitamin A is less than 70% of that required, and 5% of all children suffer from night blindness.…”
mentioning
confidence: 99%
“…Observa-se, ainda, discrepância das tendências epidemiológicas descritas quanto ao declínio da desnutrição energética e protéica no Brasil (47) . Os estudos realizados em diferentes partes do país têm sido eficazes na medida em que identificam os grupos mais vulneráveis à carência de micronutrientes (9,48,49) , não havendo diferenças marcantes na ocorrência desta deficiência entre as diversas regiões. Isso significa que a deficiência não está restrita às camadas da população menos favorecidas, indicando haver uma história independente em relação ao curso histórico da desnutrição energética e protéica.…”
Section: Discussionunclassified